Epidemiological Situation of Soft Tissue Sarcomas of The Extremities According to Histological Verification in The Republic of Uzbekistan - S.J. Sheraliyeva; D.Sh. Polatova (Zien Journals, 2023)
to evaluate the frequency of soft tissue sarcomas of the extremities by histological type
Keywords: soft tissue; morbidity; fibrosarcoma